A New Model of Body Composition Detects Association Between Severe Obesity and Increase in Skeletal Muscle Mass - Dahlmann Nicolaus; Klingmüller Dietrich (Journal of Model Based Research, 2025)
Obesity is associated with functional limitations in muscle performance. The true effect of obesity on skeletal muscle mass, including any interactions with aging effects, remains to be elucidated. The present study investigated the impact of obesity on the stimulation of muscle growth, based on a new model of body composition. A dataset of 44 men and 64 women was analysed. Body weight (Wt), body height (Ht), hand circumference (HdC) and waist circumference (WC) were measured. Processed by the Dahlmann-Body-Analysis (DBA) system, a new model of body composition, the increase of skeletal muscle mass (ΔSMM) compared to the individual reference weight was calculated. Muscle mass data derived by the DBA model are compared with DXA-derived predictive equations of studies representing different countries and ethnicities estimating the appendicular skeletal muscle mass. Means of these groups are tested by ANOVA. Age ranged from 18 to 72 years. All subjects had a BMI ≥ 29.7 (kg/m²). The mean values of ΔSMM as an estimate of muscle mass gain calculated by the DBA-system were 11.8 ±3.6 kg for men and 8.9 ±2.6 kg for women, respectively, demonstrating a linear, significantly rising relationship with BMI (ß > 0, p<0.001). The study population did not show a decrease in muscle mass with age in either men or women up to an age of 65 years. The results suggest that the present model has satisfactory prediction qualities to detect an increase in skeletal muscle mass associated with a growing burden of body fat.
Keywords: Dahlmann-Body-Analysis (DBA)